Levels of Engagement in Task-based Synchronous Computer Mediated Interaction - Torres, Julio; Yanguas, Íñigo (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
Investigating task-based synchronous computer-mediated communication (SCMC) interaction has increasingly received scholarly attention. However, studies have focused on negotiation of meaning and the quantity, focus and resolution of language related episodes (LREs). This study aims to broaden our understanding of the role of audio, video, and text SCMC conditions by additionally examining second language (L2) learners’ levels of engagement during the production of LREs as a result of interactive real-world tasks. We tested 52 dyads of L2 Spanish intermediate learners who completed a decision- making/writing task. Our main analysis revealed that dyads in the audio SCMC condition engaged in more limited LREs vis-à-vis the text SCMC group, and audio SCMC dyads also showed a trend of engaging more in elaborate LREs. The findings imply that interactive SCMC conditions can place differential demands on L2 learners, which has an effect on the ways in which L2 learners address LREs during task-based interaction.